Estudio comparativo de los trastornos de ansiedad y depresión que presentan los pacientes diagnosticados con hipotiroidismo y diabetes en el servicio de endocrinología del Hospital Isidro Ayora de Loja. Lineamientos alternativos. Periodo enero-abril 2015 - González Loján, Nohely Gabriela (2015)
It is necessary to analyze that in the vital process of the human being there exist multiple factors that can cause an instability in its emotional state, it is so the fact of enduring an illness endocrine or metabolic it can motivate the appearance of diverse pathologies of psychological order as the depression and anxiety. This research work has been developed in order to carry out a comparative study of disorders of anxiety and depression with patients diagnosed with hypothyroidism and diabetes; establish the average number of patients who have diabetes and hypothyroidism; check the average number of patients who have anxiety and depression; develop a plan of action to improve the States of anxiety and depression in these patients. Inductive, statistical and descriptive method was used in the research. According to the data obtained was determined that there is a predominance of anxiety disorders, followed by depression and joint disorders, anxious disorders depressive, noting the presence of affective disorders in degenerative diseases. The scenario where this investigative work was generated was in the Area of outpatient "Isidro Ayora" General Hospital in the city of Loja, where applied psychological reagents, the Hamilton anxiety scale and the Beck Depression inventory, to make comparative study in these pathologies. Key words: Anxiety, Diabetes and hypothyroidism.